Analisis Neraca Air Pada SUB-KHG 1 Pulau Padang, Kabupaten Kepulauan Meranti, Provinsi Riau - Putri, Tasha Ramadhery; Sutikno, Sigit; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
More than 40% of Padang Island area has been concessioned by the Ministry of Forestry to PT. RAPP. The construction of large-scale canalization of peatland utilization adopted by the company’s concessions causes disruption of the water balance. Research at Peat Hydrological Unit (PHU) Padang Island isnecessary so that peatland protection and restoration become more efficient and effective. The method used in this study is Thornthwaite Mather Water Balance (TMWB). Water balance depicted in a temporal graph showing the deficit/surplus status in every month and Geographic Information System (GIS) used for spatialdata analysis at PHU Padang Island. The results of land water balance analysis in PHU at 2020, shows that the highest drought (deficit) level was in the Sub-PHU 1 on February with the 26.83 million m3. For the highest wetness (surplus) level was in the Sub-PHU 1 on November with 31.34 million m3.Keywords : deficit, Peat Hydrological Unit, surplus, Thornthwaite Mather Water Balance, water balance.